Deriving color adjectival nominalizations - Alexiadou, Artemis (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
In this paper I examine two types of nominalizations related to color adjectives in Greek, a suffixed one and a neutral one, which I will compare to their English and Dutch (and German) counterparts. I show that the two differ in that suffixed nominalizations denote stage level properties, while neuter nominalizations denote individual level properties. This difference is due to the fact that suffixed nominalizations are count nouns, while neuter nominalizations are mass nouns. A comparison between Greek, and Dutch/German and English shows that languages have different nominalization strategies: nominalization can take place at three layers: at the root level, at the nP level, and finally at the DP level. This explains the differences in distribution and interpretation among the different nominalization types across languages.